Challenges and Opportunities in Implementing Renewable Energy in Iraq - Al-Ghabera, Hassan; Hassan Ahmed, Rania; Youssef, Mariam; Mahmood, Abbas (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2024)
This research explores the potential of renewable energy in Iraq, focusing on the challenges and opportunities for its implementation to address the country’s energy crisis. Iraq, historically reliant on oil and gas, faces severe energy shortages and infrastructure damage due to years of conflict. The objective of this study is to investigate how renewable energy, particularly solar and wind power, can provide a sustainable solution to Iraq's energy demands. The research employs a mixed-methods approach, utilizing in-depth interviews with energy experts, surveys of the general public and industry stakeholders, and case studies from countries like Morocco and Tunisia that have successfully implemented renewable energy systems. The findings highlight the significant potential for solar and wind energy in Iraq, but also emphasize the barriers related to infrastructure, policy uncertainty, and investment shortages. The study suggests that while renewable energy can play a key role in Iraq’s energy future, it requires strong governmental policies, infrastructure improvements, and private sector investments to succeed. Cultural and economic factors must also be considered for successful adoption. The discussion underscores the need for a strategic approach to integrate renewable energy into Iraq’s energy sector. Future research should explore the feasibility of specific renewable energy projects, focusing on policy frameworks, technological advancements, and the role of international partnerships in accelerating renewable energy development.